Optical Properties of Living Corals Determined With Diffuse Reflectance Spectroscopy - Jacques, Steven L.; Wangpraseurt, Daniel; Kühl, Michael (Frontiers in Marine Science, 2019)
The internal light field and thus light exposure of the photosymbiotic microalgae (Symbiodinium sp.) in corals is strongly modulated by the optical properties of coral tissue and skeleton. While there are numerous studies documenting the light microenvironment in corals, there are only few measurements of the inherent optical properties of corals in the literature, and this has hampered a more quantitative understanding of coral optics. Here we present a study of the optical properties of 26 live coral samples, representative of 11 coral species and spanning a variety of morphotypes. We employed well-established fiber-optic reflectance spectroscopy techniques from biomedical optics using two methods: (1) A source and a detection fiber separated by a variable distance measured the lateral spread of light in corals, dominated by the skeleton; (2) A fiber-optic field radiance probe measured the diffuse reflectance from the coral surface, dominated by the living coral tissue. Analysis based on diffusion theory and Monte Carlo simulation yielded estimates of the bulk scattering and absorption coefficients of the coral tissue and skeleton, in the 750-1030 nm wavelength range. Extrapolating into the spectral region of photosynthetically active radiation (PAR, 400-700 nm) allowed estimation of the optical depth of absorption by the main Symbiodinium photopigment chlorophyll a. Coral tissue scattering was on average ~1.9x stronger than the scattering of the skeleton, consistent with the model that corals trap photons by high scattering to enhance absorption by algal pigments, while the lower scattering of the skeleton allows spread of light to otherwise shaded coral tissue areas.